THE ROLE OF SELF-MANAGEMENT IN REDUCING WORK STRESS CAUSED BY ROLE CONFLICT, ROLE AMBIGUITY, TIME PRESSURE AND WORK OVERLOAD: EMPIRICAL EVIDENCE FROM PAKISTAN - Rafiq, Dr. Imran; Aleem, Muhammad; Mordhah, Dr. Najwa; Sajid, Rehan; Ziauddin, (The journal of contemporary issues in business and government, 2021)
The purpose behind this research was to observe the role of self-management in reducing work stress caused by common stressors (Role Conflict, Role Ambiguity, Time Pressure and Work Overload). Stress is a growing concern in a walk of life, the causes of stress are so many specifically the work stress is researched so muchdue to the significant impact of this on all important variables of business and life in general.It is always an interesting quest to find the remedy for such issues, for this purpose the emotional intelligence is considered the best copy strategy. This research aims at finding the role of second dimensions of emotional intelligence (self-management) which was taken as the independent variable and 2nd order variable technique were used to obtain the work stress from the four stressors. The smart pls 3.0 software was used to achieve the path coefficients (-0.179,-0.321,-0.285,-0.358)(Role Conflict, Role Ambiguity, Time Pressure and Work Overload) respectively. R square (0.032, 0.103, 0.081, 0.128), T statistic (3.510, 6.775, 6.049, 7.333) and p-value (0.000, 0.000, 0.000, 0.000). This study was conducted in the hospital setting of three main hospitals in district Peshawar namely lady reading, Khyber teaching and Hayatabad medical complex. The sample size of 361 nurses and medical staff was obtained using stratified and systematic random sampling techniques.